Organic Imagery in the Novel If Cats Disappeared From The World - Rico Jonssa Aditya; Maharani, Putu Devi; Suastini, Ni Wayan (Institut Pariwisata dan Bisnis Internasional, 2024)
The title of this study is “Organic Imagery in the Novel Entitled If Cats Disappeared From The World”. This study focused on the analysis of organic imagery in the novel entitled If Cats Disappeared From The World. The objective of this study is to classify and identify the dominant feelings of the organic imageries in the novel entitled If Cats Disappeared From The World. This study used the theory by Perrine in Johnson & Arp (2017) about the types of imagery, specifically organic imagery as the guidance in conducting the analysis. The data of this study were collected by using observation method and analyzed by using qualitative research method. The finding of this study were presented in formal and informal method. The result of this study showed that there are a total of 95 organic imageries found in the novel entitled If Cats Disappeared From The World. The types of feeling within the organic imagery include the feeling of happiness, sadness, anger, depression, surprisement, embarrassment, amazement, fear, maturity, and pain. Based on the result of this study, the study concluded that organic imagery is used in the novel entitled If Cats Disappeared From The World to focus the depiction of the main character through his thoughts and feelings to match with the theme of the novel.